Global and regional estimates and projections of diabetes-related health expenditure: Results from the International Diabetes Federation Diabetes Atlas, 9th edition. (April 2020) - Williams, Rhys; Karuranga, Suvi; Malanda, Belma; Saeedi, Pouya; Basit, Abdul; Besançon, Stéphane; Bommer, Christian; Esteghamati, Alireza; Ogurtsova, Katherine; Zhang, Ping; Colagiuri, Stephen
Abstract: Aims: Diabetes and its complications have a significant economic impact on individuals and their families, health systems and national economies. Methods: The direct health expenditure of diabetes was calculated relying on the following inputs: diagnosed and undiagnosed diabetes prevalence estimates, United Nations population estimates, World Health Organization health expenditure per capita and ratios of health expenditure for people with diabetes compared to people without diabetes. Results: The estimated global direct health expenditure on diabetes in 2019 is USD 760 billion and is expected to grow to a projected USD 825 billion by 2030 and USD 845 billion by 2045. There is a wide variation in annual health expenditures on diabetes. The United States of America has the highest estimated expenditure with USD 294.6 billion, followed by China and Brazil, with USD 109.0 billion and USD 52.3 billion, respectively. The age group with the largest annual diabetes-related health expenditure is 60–69 years with USD 177.7 billion, followed by 50–59 years, and 70–79 years with USD 173.0 billion and USD 171.5 billion, respectively. Slightly higher diabetes-related health expenditure is seen in women than in men (USD 382.6 billion vs. USD 377.6 billion, respectively). The same difference is expected to be present in 2030 and 2045. Conclusions: There were large disparities between high-, middle- and low-income countries with total health expenditures in high-income countries being over 300 times those in low-income countries. The ratio for annual direct health expenditure per person between these groups of countries is more than 38-fold.